2014
DOI: 10.4314/mejs.v6i1.102414
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield of barley (<i>Hordeum vulgare L</i>.) as affected by nitrogen and phosphorus fertilization and water regimes in Tigray, Ethiopia

Abstract: The understanding of the interactive effects of abiotic stresses is a crucial issue for improving cereal production in arid environment. For this reason, study was conducted in northern Ethiopia, Tigray region in three sites characterized by different climatic conditions during the cropping season of 2009/10 to understand the agronomic responses of the barley crop to nitrogen and phosphorus fertilization rates combined with supplementary irrigation. Nitrogen (N) and phosphorus (P) fertilizers were applied unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…These results are in accordance with those obtained by Shafi et al (2011), Jankovic et al (2011), Seadh et al(2017, Dubey et al(2018) and Kassie and Tesfadye (2019). Meanwhile, Mengistu and Abera (2014) and Terefe et al (2018) reported that 1000 seed of malt barley weights had a linear and negative response to N fertilizer rates and exhibited non-significant difference among control and the rest of applied N treatments.…”
Section: Nitrogen Fertilization Effectmentioning
confidence: 99%
“…These results are in accordance with those obtained by Shafi et al (2011), Jankovic et al (2011), Seadh et al(2017, Dubey et al(2018) and Kassie and Tesfadye (2019). Meanwhile, Mengistu and Abera (2014) and Terefe et al (2018) reported that 1000 seed of malt barley weights had a linear and negative response to N fertilizer rates and exhibited non-significant difference among control and the rest of applied N treatments.…”
Section: Nitrogen Fertilization Effectmentioning
confidence: 99%
“…The higher yield component of subsequent wheat crop observed in the faba bean-wheat rotation can be due to better BNF of faba bean [ 16 ]. Several research findings also confirmed that soil N obtained from BNF significantly improved vegetative growth and biomass of wheat [ [26] , [27] , [28] ]. The legume residues and BNF have also increased grain yield of subsequent wheat crop.…”
Section: Discussionmentioning
confidence: 65%